Incidence Of Different Hepatic Lesions in Saudi Patients Using Computed Tomography - Mahmoud, Mustafa Z.; Fagiri3Maram A.; Ghamdi, Walid Al-; Qahtani, Khalid Al- (Asian Journal of Medical Radiological Research, 2014)
Computed tomography (CT) scanning is a noninvasive medical test that helps physicians to diagnose and treat medical conditions. This study was designed with an aim to determine the incidence of different hepatic lesions in Saudi patients whom presents at the Radiology Department of King Khalid Hospital at Al-Kharj province, when the liver is investigated using CT modality. CT scanner used was Siemens Somatom Emotion. Scanner features include 70 cm aperture, 50 cm scan field and a patient table that can hold patients up to 440 pounds. Also it offers reconstructed on the fly with up to 16 images per second. Out of hundred examined samples [male to female ratio of 1.2:1] hepatic adenoma (1%) and fatty fibrotic changes (2%) were the least benign lesions detected, while hepatocellular carcinoma (HCC) was the commonest malignant lesion (34.5%) found in the samples.Metastatic liver lesions and HCC were the commonest malignant lesions detected in the livers of Saudi patients.